First Photographic Record of Little Pied Flycatcher Ficedula westermanni from Badalkhol Wildlife Sanctuary, Jashpur, Chhattisgarh, India - Rai, Abhay; Kumar, Atul; Naidu, Ravi; Vishwakarma, Anurag (Journal of the Bombay Natural History Society (JBNHS), 2023)
No Abstract.